Designing TRiDS: Treatments for Risks in Design Science - Venable, John; vom Brocke, Jan; Winter, Robert (Australasian Association for Information Systems and Australian Computer Society, 2019)
Design Science Research (DSR) has many risks. Researchers inexperienced in DSR, especially early career researchers (ECRs) and research students (e.g. PhD students) risk inefficient projects (with delays, rework, etc.) at best and research project failure at worst if they do not manage and treat DSR risks in a proactive manner. The DSR literature, such as the Risk Management Framework for Design Science Research (RMF4DSR), provides advice for identifying risks, but provides few suggestions for specific treatments for the kinds of risks that potentially plague DSR. This paper describes the development of a new purposeful artefact (TRiDS: Treatments for Risks in Design Science) to address this lack of suggestions for treatment of DSR risks. The paper describes how the purposeful artefact was developed (following a DSR methodology), what literature it draws upon to inspire its various components, the functional requirements identified for TRiDS, and how TRiDS is structured and why. The paper also documents the TRiDS purposeful artefact in detail, including four main components: (1) an extended set of risk checklists (extended from RMF4DSR), (2) a set of 47 specific suggestions for treating known risks in DSR, (3) a classification of the treatments identified into 14 different categories, and (4) a look-up table for identifying candidate treatments based on a risk in the extended risk checklists. The treatment suggestions and guidance in TRiDS serve as a supplement to RMF4DSR by helping DSR researchers to identify treatments appropriate for a particular DSR project (or program) and thereby to improve DSR project efficiency and the probability of DSR project success.